The Role of Mesenchymal Stem Cell Secretome and Extracellular Vesicles in Targeting Emerging and Persistent Viral Reservoirs Beyond Respiratory Viruses: A Narrative Review - Nur Dina Amalina; Faya Nuralda Sitompul; Ririn Rahmala Febri; Farahana Kresno Dewayanti; Izzati Rafidah; Fitri Hasnaulia Wargadipura (International Journal of Cell and Biomedical Science, 2025)
Background: Persistent viral infections remain a significant global health challenge, with viral reservoirs in anatomically and immunologically privileged sites evading conventional therapeutic approaches. Mesenchymal stem cells (MSCs) and their secreted factors, including the secretome and extracellular vesicles (EVs), have emerged as promising therapeutic modalities due to their immunomodulatory, anti-inflammatory, and tissue-regenerative properties. Objective: This narrative review synthesizes current evidence on the therapeutic potential of MSC-derived secretome and EVs in targeting viral reservoirs beyond respiratory infections, including human immunodeficiency virus (HIV), hepatitis viruses, herpesviruses, and emerging arboviruses. Methods: A comprehensive literature search was conducted across PubMed, Scopus, and Web of Science databases for studies published between 2015 and 2025, focusing on MSC secretome, extracellular vesicles, viral reservoirs, and persistent viral infections. Results: MSC secretome and EVs demonstrate multifaceted antiviral mechanisms including direct viral inhibition, immunomodulation of host responses, tissue repair of virus-induced damage, and potential targeting of latent viral reservoirs. Evidence from in vitro, animal models, and limited clinical studies suggests efficacy against HIV latent reservoirs, chronic hepatitis B and C infections, cytomegalovirus reactivation, and dengue-induced pathology. Key bioactive components include microRNAs, cytokines, growth factors, and antimicrobial peptides that collectively modulate viral replication and host immunity. Conclusion: MSC-derived therapeutics represent a novel approach to addressing persistent viral infections, although significant challenges remain in standardization, scalability, delivery methods, and clinical translation. Future research should focus on optimizing EV production, identifying specific bioactive components, elucidating the mechanisms of reservoir penetration, and conducting rigorous clinical trials to establish the efficacy and safety profiles of these products.